2021
DOI: 10.2478/kom-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Terephthalohydrazide and isophthalo- hydrazide as new corrosion inhibitors for mild steel in hydrochloric acid: Experimental and theoretical approaches

Abstract: Most organic corrosion inhibitors have polar groups through which the molecule can be adsorbed strongly or specifically on the metal surface. In this investigation, terephthalo- hydrazide and isophthalohydrazide were synthesized as corrosion inhibitors, and their corrosion-inhibiting properties on mild steel were evaluated in a corrosive environment by weight loss measurements. The results of corrosion experiments revealed that terephthalohydrazide and isophthalohydrazide as inhibitors controlled or reduced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…As shown in Table 1 , most of the tested heterocyclic organic compounds have significant inhibitory efficacy. PMBMH has the strongest inhibitory ability of the heterocyclic organic compounds reported in Table 1 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], with a performance equivalent to those reported in [ 15 , 23 , 26 , 28 ]. As the concentration of PMBMH increases, the rate of corrosion decreases, and the inhibitive efficacy improves.…”
Section: Resultsmentioning
confidence: 74%
“…As shown in Table 1 , most of the tested heterocyclic organic compounds have significant inhibitory efficacy. PMBMH has the strongest inhibitory ability of the heterocyclic organic compounds reported in Table 1 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], with a performance equivalent to those reported in [ 15 , 23 , 26 , 28 ]. As the concentration of PMBMH increases, the rate of corrosion decreases, and the inhibitive efficacy improves.…”
Section: Resultsmentioning
confidence: 74%
“…In the latest study by Al-Baghdadi et al [44] in 2021, new hydrazide derivatives, terephthalohydrazide, and isophthalohydrazide were investigated for their application as corrosion inhibitors for mild steel in a corrosive environment. The investigation findings revealed that terephthalohydrazide and isophthalohydrazide could control and reduce corrosion through adsorption mechanism showing remarkable inhibition efficiencies of 96.4% and 97.2%, respectively, at the optimum concentration of 0.5 mM.…”
Section: Fatty Hydrazides Derivatives As Effective Corrosion Inhibitorsmentioning
confidence: 99%
“…DFT enables the accurate prediction of stability, chemical reactivity, and inhibition efficiency without using expensive chemicals and time- consuming laboratory testing. 6,7 For instance, Preethi Kumari et al 8 Similarly, Al-Baghdadi et al 9 investigated terephthalohydrazide and isophthalohydrazide in silico and discovered the compounds to be excellent CIs. Terephthalohydrazide and isophthalohydrazide were experimentally shown to exhibit inhibitive efficiencies up to 97.2% at the optimum concentration of 0.5 mM in HCl conditions.…”
Section: Introductionmentioning
confidence: 99%